A Study of Bending Property for Glass Fiber Reinforced Thermoplastic Composite Sheets - Zaidan, Mustafa Faisal; J. Jadee, Khudhayer; A. Abed, Salwa (International Journal of Scientific Research and Management (IJSRM), 2019)
In this research a study of the influence of percentage for chopped fiber glass reinforcement thermoplastic sheet on the flexural strength. Hot compression method used to fabricate thermoplastic (polypropylene and polyamide) reinforced by fiber glass at different percentage (10,20,30,40) wt.%, the flexural strength test done by using three-point bending test. The results shown that for bending test the sample glass fiber reinforcement polyamide (GFRPA) and sample glass fiber reinforcement polypropylene (GFRPP), which reinforced with 40% fiber glass achieved the high magnitude of flexural strength (106.1 and 70.8) MPa respectively. While the sample polyamide (PA) and polypropylene (PP) without reinforcement show the lowest magnitude of flexural strength (59.5 and 38.4) MPa respectively.